Spectrum of uterine lesions presenting as abnormal uterine bleeding in a rural north Indian population: a study from tertiary care center - Singh, Shruti; Pandey, Pinki; Agarwal, Savita; Swarn, Kaur; Singh, Sanjeev (International Journal of Research in Medical Sciences, 2017)
Background: Abnormal uterine bleeding (AUB) is now a day’s one of the commonest complains of female patients attending gynaecological OPD and clinics. The problem is not limited to a particular age group and frequently affects reproductive age group as well as peri and postmenopausal females. Endometrial biopsy or curettage is a well-known safe and effective diagnostic procedure in evaluation of abnormal uterine bleeding and ruling out medical causes. Methods: The study was undertaken to ascertain cause of AUB in all patients presenting at gynecology OPD with complain of abnormal uterine bleeding during the period of January 2013 to January 2014. Relevant clinical data was collected in all cases and endometrial biopsy or hystrectomy specimens were taken for histopathological evaluation. Results: Maximum number of AUB cases (34%) were seen in the age group of 41-50 years of age and predominant histopathological pattern observed was proliferative endometrium seen in 18% cases. Leimyoma is another important leading cause followed by bleeding in secretory phase and others. Menorhhagia was the most common clinical presentation. Benign conditions and pregnancy related causes occur mostly in the reproductive age group while premalignant and malignant changes occur in premenopausal and postmenopausal age group. Conclusions: A thorough clinical history, etilogical factors, ultrasound findings along with clinical presentation are important along with histopathological examination which plays a key role in early and prompt diagnosis of abnormal uterine bleeding.